2015
DOI: 10.1111/josi.12147
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Parental Approval and Disapproval for Black and White Interracial Couples

Abstract: Black and White interracial couples encounter societal and familial assessments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 24 publications
1
41
1
Order By: Relevance
“…The challenge is to help partners realize that both “truths” can coexist based on their lived experience. (For additional discussion of the impact of microaggressions on interracial couples, see the Castle Bell & Hastings, article on parental approval and disapproval in this volume).…”
Section: Unique Clinical Issues For Interracial Couplesmentioning
confidence: 99%
“…The challenge is to help partners realize that both “truths” can coexist based on their lived experience. (For additional discussion of the impact of microaggressions on interracial couples, see the Castle Bell & Hastings, article on parental approval and disapproval in this volume).…”
Section: Unique Clinical Issues For Interracial Couplesmentioning
confidence: 99%
“…() and Craig‐Henderson and Lewis () suggested that researchers need to examine interethnic couples using prospective or longitudinal methods. This would be especially helpful in understanding the role of the social network (Castle Bell and Hastings, ; Leslie and Young, ) and changes in racial identity of the partners (Afful et al., ). Perhaps there is disapproval of some in the social network early in the marriage, but these perceptions become more positive over time.…”
Section: Closing Thoughts On Future Researchmentioning
confidence: 99%
“…Castle Bell and Hastings (2015) cite prior research suggesting that social disapproval, marginalization, and lack of validation of interethnic couples is not uncommon. As noted by Leslie and Young (2015), these disapprovals may be blatant or take the form of microaggressions.…”
Section: Costsmentioning
confidence: 99%
See 2 more Smart Citations